Food insecurity and ultra-processed food consumption in the Health and Retirement Study: Cross-sectional analysis - Abeer A. Aljahdali (The Journal of Nutrition, Health and Aging)
Background: Higher ultra-processed foods (UPF), attributed to more than half of daily intake in the US, have been associated with impaired health outcomes. Documented evidence highlights disparities in UPF consumption due to food insecurity, which is a public health challenge among older adults in the US. Objectives: The study examined the link between food insecurity and UPF consumption. The potential of participants’ sex, age, and race and Supplemental Nutrition Assistance Program (SNAP) participation in modifying the association were explored. Method: The analytical sample comprised 6295 US adults, aged 52 – 101 years, enrolled in the longitudinal Health and Retirement Study (HRS), a nationally representative study of aging. Food insecurity was evaluated in the 2013 HRS Health Care and Nutrition Study using the six-item Short Form Food Security Survey Module. Dietary intake was assessed using a food frequency questionnaire, and UPFs, quantified using the NOVA food classification system, were expressed as a percentage of total energy intake. The association between food insecurity and UPFs was examined using linear regression models, adjusted for sociodemographic characteristics. Results: The prevalence of food insecurity was 15%. Mean UPFs% (95% confidence intervals) were 49.1 (47.8, 50.3), 48.5 (46.6, 50.4), and 52.3 (50.4, 54.3) among adults with food security, low food security, and very low food security, respectively (P-trend = 0.0156). Race modifies the association between food insecurity and UPFs (P-interaction = 0.0033). A positive linear trend was detected among Whites (P-trend = 0.0036), but an inverse linear trend was found among African Americans (P-trend = 0.0007). There was no evidence for heterogeneity by age, sex, or SNAP participation. Conclusion: Food insecurity was positively correlated with UPF consumption among adults in the US. Race modifies the association with a positive linear trend among Whites and an inverse linear trend among African Americans. Further efforts are needed to promote healthy aging via improving diet quality among food-insecure older adults.